Annual Report, 1988-89 - Bangladesh Agricultural Research Council (Bangladesh Agricultural Research Council : Framgate, 1989)
This report summarizes the activities of the South Carolina Office of Instructional Technology during the 1988-89 school year. Objectives relating to planning, fiscal management, administration, computers, evaluation, dissemination, and reporting for the office's Annual Management Plan are outlined. An advisory system designed to facilitate communication between the office and schools is described, and 13 publications available from the office are listed. Primary activities in computer-assisted instruction are discussed, including the revision of software advisory listings and conducting the sixth annual statewide computer survey. Brief descriptions of instructional television (ITV) and radio resources developed by the Resource Development Section follow. Other activities of this section are noted, e.g., program evaluation, workshops, and new staff development resources. Data are also reported for major accomplishments of the Utilization Section inservice and training utilization, utilization services provided, television network expansion, equipment purchases, computer education utilization, and the Software Evaluation Exchange Dissemination project. The results of the annual survey of ITV and radio usage, ITV utilization history, ITV utilization trends, and staff development utilization are covered, and conferences/workshops and teleconferences are listed. Results of the annual computer survey are shown and compared with those of previous years. Activities aimed at increasing awareness of ITV and radio are summarized. Plans for 1989-90 to improve utilization and reception conclude the report. (MES)
Microfiche.
Keywords: Annual Reports; South Carolina Department of Education; Interactive Television; Reports, Descriptive